Socially responsible investing as a competitive strategy for trading companies in times of upheaval Amid COVID-19: Evidence from Spain - Jesús Manuel Palma-Ruiz; Julen Castillo-Apraiz; Raúl Gómez Martínez (International Journal of Financial Studies, 2020)
Sustainable and responsible investing (SRI) is a strategy that seeks to combine both financial return and social good. The need to create and preserve SRI represents a key argument in investment decision-making, which leads other firms and investors to make strategic decisions beyond financial logic, based on environmental, social, and governance (ESG) factors. Within this framework, this paper aims to further clarify the understanding of potentially profitable strategies for firms during a global crisis such as a pandemic. Both primary and secondary data were gathered, and descriptive analyses were conducted. In Spain, several IBEX-35 companies announced donations amid the COVID-19 crisis. First, companies were classified into two groups based on donations made. For this, we searched for ESG online news. Then, profitability records amongst companies were identified and compared. In the trading session after the announcements, we found 12 of the 35 companies that made donations had a higher performance index of more than 2 and 3 points over the companies that did not make donations. With a weekly perspective, the difference was 91 and 60 basis points, respectively. These results suggest that in times of upheaval, investors base their strategy on ESG factors, contributing to the emerging literature on individual motives of SRI. Second, by conducting a survey and collecting data from 575 Spanish citizens, we conclude that after this crisis, people's perceptions towards corporate social responsibility (CSR) will change, affecting consumption preferences in those companies that exhibited socially irresponsible or unsupportive behaviour. Hence, the reputation of firms, their social image, and social trust will play an important role in the near future.
Keywords: M14; G21; O35; 330; socially responsible investing; corporate social responsibility; strategic management; performance; COVID-19